Psychological Features of Adolescence (Eurasian Research Bulletin, 2022)
The article discusses adolescence and its specific features, and the physical, spiritual and anatomical changes that occur in the adolescent psych. It also provides an analysis of their psychological characteristics, which are characteristic of cognitive processes.